Significant hospitalization cost savings to the payer with a pharmacist‐led mobile health intervention to improve medication safety in kidney transplant recipients. Issue 10 (14th July 2021) - Taber, David J.; Fleming, James N.; Su, Zemin; Mauldin, Patrick; McGillicuddy, John W; Posadas, Aurora; Gebregziabher, Mulugeta
Abstract : This was an economic analysis of a 12‐month, parallel arm, randomized controlled trial in adult kidney recipients 6 to 36 months posttransplant (NCT03247322). All participants received usual posttransplant care, while the intervention arm received supplemental clinical pharmacist‐led medication therapy monitoring and management, via a smartphone‐enabled mHealth app, integrated with risk‐based televisits. Hospitalization charges were captured from the study institution accounts payable and non‐study institution hospitalization charges were estimated using multiple imputation. Multivariable modeling was used to assess the impact of the intervention on charges. The intervention significantly reduced rates of hospitalization (1.08 per patient‐year in the control arm vs 0.65 per patient‐year in the intervention arm, p = .007). The control arm had estimated hospitalization costs of 870, 468 vs 390, 489 in the intervention arm. Modeling demonstrated a 49% lower hospitalization charge risk in the intervention arm (RR 0.51, 95% CI 0.28‐0.91; p = .022). From a payer or societal perspective, the net estimated cost savings, after accounting for intervention delivery costs, was 368, 839, with a return on investment (ROI) of 4.30 for every 1 spent. These results demonstrate that a mHealth‐enabled, pharmacist‐led intervention significantly reduced hospitalization costs for payers over a 12‐month period and has a positive ROI. Abstract : Economic analysis of a randomized, controlled, 12‐month trial in adult kidney recipients testing a pharmacist‐led mobile health intervention demonstrates substantial reduction in hospital costs and positive return on investment.